Role for intraflagellar transport in building a functional transition zone. (14th November 2018) - Jensen, Victor L; Lambacher, Nils J; Li, Chunmei; Mohan, Swetha; Williams, Corey L; Inglis, Peter N; Yoder, Bradley K; Blacque, Oliver E; Leroux, Michel R
Abstract: Genetic disorders caused by cilia dysfunction, termed ciliopathies, frequently involve the intraflagellar transport (IFT) system. Mutations in IFT subunits—including IFT‐dynein motor DYNC2H1—impair ciliary structures and Hedgehog signalling, typically leading to "skeletal" ciliopathies such as Jeune asphyxiating thoracic dystrophy. Intriguingly, IFT gene mutations also cause eye, kidney and brain ciliopathies often linked to defects in the transition zone (TZ), a ciliary gate implicated in Hedgehog signalling. Here, we identify a C. elegans temperature‐sensitive ( ts ) IFT‐dynein mutant ( che‐3 ; human DYNC2H1) and use it to show a role for retrograde IFT in anterograde transport and ciliary maintenance. Unexpectedly, correct TZ assembly and gating function for periciliary proteins also require IFT‐dynein. Using the reversibility of the novel ts ‐IFT‐dynein, we show that restoring IFT in adults (post‐developmentally) reverses defects in ciliary structure, TZ protein localisation and ciliary gating. Notably, this ability to reverse TZ defects declines as animals age. Together, our findings reveal a previously unknown role for IFT in TZ assembly in metazoans, providing new insights into the pathomechanism and potential phenotypic overlap between IFT‐ and TZ‐associated ciliopathies. Synopsis: A temperature‐sensitive mutation in C. elegans CHE‐3, the orthologue of mammalian DYNC2H1, reveals a role for the intraflagellar transport (IFT) retrograde dynein motor in anterograde IFT transport, cilium structure maintenance, and assembly of a functional transition zone ("ciliary gate"). Reversible temperature‐sensitive ( ts ) IFT‐dynein ( che‐3 ) mutant uncovered in C. elegans . Loss of CHE‐3 function abrogates retrograde IFT and eventually halts anterograde IFT. CHE‐3 is required for cilium structure maintenance. CHE‐3 facilitates assembly and function of the transition zone "ciliary gate". Abstract : A temperature‐sensitive mutation in the gene encoding the C. elegans Dynein‐2 heavy chain, CHE‐3, reveals a role for the retrograde dynein motor in anterograde intraflagellar transport, cilium structure maintenance, and assembly of a functional transition zone.